Acute oxalate nephropathy: A potential cause of acute kidney injury in diabetes mellitus—A case series from a single center - Bao, Daorina; Wang, Yu; Yu, Xiaojuan; Zhao, Minghui (Frontiers in Medicine, 2022)
Background: Acute oxalate nephropathy (AON) is an uncommon condition that causes acute kidney injury (AKI), characterized by massive deposition of calcium oxalate crystals in the renal parenchyma. Urinary oxalate excretion has been found to be increased in patients with diabetic mellitus (DM) in previous studies. Here, we report a case series of diabetic AKI biopsy-proven AON, aiming to alert physicians to the potential of AON as a trigger of AKI in diabetic patients in clinical practice. Methods: Cases with a pathological diagnosis of AON, who presented with AKI clinically and had DM between January 2016 and December 2020 were retrospectively collected. Their clinical manifestations, natural history and prognosis were also recorded. Results: Six male patients with biopsy-proven AON were identified, aged 58.39.1 years at the time of kidney biopsy. Only one patient who had received Roux-en-Y gastric bypass surgery took oxalate-rich food before the onset of the disease. None of them had clinical features of enteric malabsorption. Three patients were on renin-angiotensin system inhibitor treatment for hypertension comorbidity, and 5 of them received nonsteroid anti-inflammatory drugs. Three patients presented with oliguria, with peak creatinine ranging from 463 to 1641mol/L. Four patients received renal replacement therapy at the beginning, and none required dialysis at discharge. Four patients received a course of corticosteroid treatment, two of whom had kidney function recovery, while the others had residual kidney dysfunction. One of the 2 remaining patients without corticosteroid treatment fully recovered, while the other patient achieved partial recovery at the last follow-up. Conclusion: Acute oxalate nephropathy might be a rare but potentially trigger of acute kidney injury in patients with diabetes mellitus. Kidney biopsy could help physicians to make the correct diagnosis. The proper treatment to alleviate oxalate-induced injury needs to be studied further.